37 The development and set-up of a novel radionuclide therapy service using radiation synovectomy to treat haemophilic synovitis. (4th October 2017) - Thurlow, B; Price, L; Hubert, N; Biassoni, L
Abstract : Background: Repetitive joint bleeding leading to chronic synovitis and progressive arthropathy are the hallmarks of severe haemophilia and a major cause of disability in patients with this coagulopathy. Haemophilic synovitis is usually prevented by prophylactic clotting factor replacement and bypassing agents. However, a small number of patients have inhibitory antibodies to factor replacement and develop one or more target joints with chronic synovitis. Our aim was to set-up a novel radionuclide therapy service (our first at GOSH) using radiation synovectomy as an alternative treatment option to treat children with haemophilic synovitis. Methods: A multi-disciplinary group was formed to develop this service utilising a collaborative approach between haemophilia, physiotherapy and radiology. The intervention involves injecting Re 186 into the joint capsule within interventional radiology to cause coagulation necrosis of the synovial tissue through β-irradiation. The λ-emission is then imaged using SPECT CT to assess the bio-distribution of the radio-colloid and detect any extra-articular radioactivity. Results: This service development was presented as a QIPP to the CCG. The approval for this therapy was based on its close alignment with efficiency and value strategies in delivering a personalised effective treatment for the patient with minimal inpatient stay, whilst significantly reducing the costs associated with prophylactic clotting factor. Conclusions: This therapy should be most effective in grade I and II synovitis and it is anticipated that it will reduce the frequency of haemarthrosis and prevent progression to haemophiliac arthropathy. At present, 8 patients have been identified and accepted for this therapy under the referral criteria, with the service due to commence imminently. The intervention outcome parameters will be measured by; 1.Future joint bleed frequency, 2. Pre and post MR imaging to assess synovial thickness, 3. Joint pain scores, and 4.Physical objective and functional measures. Patient reported outcomes (PROMs) will be used to assess impact on quality of life.